Credit Control Management and Business Performances: The Malaysian Family SMEs Perspectives - Khin, Edward Wong Sek; Loong, Chong Kei; Singh, Gurcharan (UI Scholars Hub, 2015)
This study examined the relationship between control management and family business performance in the Malaysian context. It has two objectives, the first being to determine the relationship of organizational credit control policy and procedures, employee development and motivation, and intelligence collection systems to subsequent collection reports in Malaysian family SMEs. The second objective is to investigate the moderating effect of participation in decision-making and work effort towards innovation and business performance. This is a descriptive study involving 90 senior executives employed in 90 Malaysian family SMEs/firms. A correlation analysis from this study confirmed previous researchers’ observations that high-level organizational commitment to credit control management is linked to improvements in business performance. The results suggest that three components – credit policy, employee development, and intelligence collection systems – are the most important predictors for the efficiency and effectiveness of credit control management.